Metabolomic mechanism and pharmacodynamic material basis of Buxue Yimu pills in the treatment of anaemia in women of reproductive age - Ying-ying, Guo; Yan-fang, Wang; Yan, Deng; Su-ying, Zhang; Dong, Liu; Bin, Luo; Xue, Wang; Miao, Deng; Rui-lin, Ma; Xiao-hui, Liu; Yu-pei, Jiao; Ai-jun, Sun (Frontiers in Pharmacology, 2023)
Objective: To explore the pharmacological basis and mechanism of Buxue Yimu pills (BYP) in the treatment of anaemia in women from the perspective of metabolomics and network analysis. Materials and Methods: Forty-six women of reproductive age with haemoglobin 70–110 g/L were recruited. Blood samples were collected before and after 4 weeks of oral BYP treatment to assess the changes in haemoglobin, coagulation function, and iron metabolism indices. An integrated analysis of metabolomics (liquid chromatography mass spectrometry) and network analysis was performed to identify the potential pharmacodynamic mechanisms of BYP. Results: After BYP treatment, the haemoglobin level of patients significantly increased from 93.67 ± 9.77 g/L to 109.28 ± 12.62 g/L (p < 0.01), while no significant changes were found in iron metabolism and coagulation-related indicators. A total of 22 differential metabolites were identified after metabolomics analysis, which were mainly related to the inhibition of inflammation and oxidative stress. Integrating pharmacodynamics and metabolomics, a network of drug-active components-targets-metabolic pathways-metabolomics was established. Acetylcholinesterase, phospholipase A2 group IIA, and phospholipase A2 group IVA may be the most promising therapeutic targets. Conclusion: BYP can inhibit inflammation and oxidative stress as well as promote haematopoiesis, potentially improving anaemia.